Beyond advanced stages in high-level spoken L2 French*. Issue 2 (July 2014) - LUNDELL, FANNY FORSBERG; BARTNING, INGE; ENGEL, HUGUES; GUDMUNDSON, ANNA; HANCOCK, VICTORINE; LINDQVIST, CHRISTINA
ABSTRACT The aim of this study is twofold: first, to find evidence for additional advanced stages in L2 French. The continuum of Bartning and Schlyter (2004) is taken as a point of departure. It is hypothesized that a number of linguistic criteria will account for high-level proficiency. It was earlier found that besides morpho-syntax, formulaic sequences and information structure are interesting phenomena for highly proficient learners (Bartning, Forsberg and Hancock, 2009). Three more measures are now added, i.e. perceived nativelikeness, lexical richness and fluency. The second aim of this study is to contribute to the debate on the possibility of nativelike attainment. The study shows that several measures are prone to characterise nativelike performance in highly proficient users among whom some attain nativelikeness.